Transjugular intrahepatic portasystemic stent shunting for control of acute and recurrent upper gastrointestinal haemorrhage related to portal hypertension. - Simpson, K J (1993)
The insertion of a transjugular intrahepatic portasystemic stent shunt (TIPSS) was evaluated in 22 patients with recurrent upper gastrointestinal haemorrhage related to portal hypertension (bleeding from oesophageal varices 10, gastric varices six, portal hypertensive gastropathy six). TIPSS was successfully performed electively in 15 patients and as an emergency in three patients. Twelve patients have had no further admissions with bleeding after TIPSS. Single episodes of bleeding were noted in six patients after TIPSS associated with shunt thrombosis (two), intimal hyperplasia within the shunt (two), and shunt migration (one). Another patient presented with reaccumulated ascites suggesting poor shunt function but died from massive variceal haemorrhage before further assessment could be performed. There was one death related to the procedure. Two patients developed encephalopathy after TIPSS, in one patient this was controlled by the insertion of a smaller diameter stent within the existing TIPSS. Several complications arose in earlier patients that have not recurred after modification of the initial technique. TIPSS can be life saving and is effective in controlling variceal haemorrhage and rebleeding from oesophageal or gastric varices and portal hypertensive gastropathy. Larger and longer term studies are required, however, to define the role of TIPSS in the overall management of such patients.